Implementation Of Ijarah Contract On Gold Pawn Products At Bank Syariah Indonesia Purwoharjo Banyuwangi Branch Office - Rahma, Angelina Laela; Ustanti, Mira (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to analyze the implementation of the ijarah contract on gold pawn products at Bank Syariah Indonesia (BSI) Purwoharjo Banyuwangi Branch Office. The study uses a descriptive qualitative approach with primary data sources obtained through interviews, observations, and documentation, as well as secondary data including literature studies and fatwas from the National Sharia Council (DSN) MUI. The data collection process involves structured interviews with related banks, direct observation of the implementation of gold pawn products, and documentation in the form of notes and photos. Data analysis was carried out using the Miles and Huberman theory which includes three stages: data categorization, data reduction, and drawing conclusions. The results of the study indicate that the ijarah contract is applied in gold pawn transactions as a rental mechanism for storing collateral, where the bank functions as a gold keeper without transferring ownership. This ijarah contract is carried out simultaneously with the rahn (pawn) contract, with administrative costs calculated based on the weight of the gold and rental costs (ujrah) for storing goods. The implementation of the ijarah contract in the gold pawn product at BSI Purwoharjo Banyuwangi has been in accordance with sharia principles, providing easy access to financing for customers, and ensuring transparency and security of transactions.